Online searches for SGLT-2 inhibitors and GLP-1 receptor agonists correlate with prescription rates in the United States: An infodemiological study - Dzaye, Omar; Berning, Philipp; Razavi, Alexander C.; Adhikari, Rishav; Jha, Kunal; Nasir, Khurram; Ayers, John W.; Mortensen, Martin Bødtker; Blaha, Michael J. (Frontiers in Cardiovascular Medicine, 2022)
Several clinical trials have demonstrated that many SGLT-2 inhibitors (SGLT2i) and GLP-1 receptor agonists (GLP-1 RA) can reduce the risk of cardiovascular events in patients with Type 2 diabetes and atherosclerotic cardiovascular disease. Recent reports indicate an underutilization of new cardiometabolic drugs, including SGLT2i and GLP-1 RA. We aimed to evaluate the use of online search volumes to reflect United State prescription rates. A repeated cross-sectional analysis of Google search volumes and corresponding data from the IQVIA National Prescription Audit (NPA) of pharmacy dispensing of newly prescribed drugs was performed. Monthly data for online searches and prescription between January 1, 2016 and December 31, 2021 were collected for selected SGLT2i and GLP-1 RA. Prescription data for drugs classes (SGLT2i and GLP-1 RA) and individual drugs were calculated as the total of queried data for branded drug names. Trends were analyzed for visual and quantitative correlation as well as predictive patterns. Overall, online searches increased by 114.6% (95% CI: 110.8%-118.4%) and 295.2% (95% CI: 257.7%-332.6%) for SGLT2i and GLP-1RA between 2016 and 2021. Prescription rates raised by 157.6% (95% CI: 142.2%-173.1%) and 221.0% (95% CI: 212.1%-229.9%) for SGLT2i and GLP-1RA for this period. Correlation coefficients (range 0.86-0.99) were strongest for drugs with growing number of prescriptions, for example dapagliflozin, empagliflozin, ertugliflozin, dulaglutide, and semaglutide. Online searches might represent an additional tool to monitor the utilization trends of cardiometabolic drugs. Associations were strongest for drugs with reported cardioprotective effect. Thus, trends in online searches complement conventionally acquired data to reflect and forecast prescription trends of cardiometabolic drugs.